The launch on the way to development or the „revival”... (Comparisons of theoretical and practical approaches apropos of the change and crisis management process of smes and mature companies) . - Noszkay, Erszébet (Acta Agraria Debreceniensis, 2009)
Hungarian SMEs, just like those in other EU member states, often cease for various reasons. Among these factors are many, which should not necessarily turn out this way. These factors are studied in numerous countries while the attempt is also made to create the systems of conditions for these enterprises to recover – often through various aids and supports (from public supports to non-governmental initiatives). Among other things they are trying to organize those services with the help of which – if there is the slightest hope for survival – those SMEs in trouble or having serious difficulties could avoid going down by recovering from their problematic situation and getting improvements. These days this issue comes up more and more urgently in Hungary, as well. It has quite a few signs indicating that – among other things – the reports, the enquiries and commissions of the National Association of Change and Crisis Managers (VOE), all of which – just like "thermometers" – reflect this tendency well. I have been doing research on this topic since 1993. As an expert I utilize them, and as a VOE member, vice president, then president I process the relevant Hungarian but mainly French experience on the subject. I intend to present those few theoretical and practical results and applicable experience I have reached this way in this presentation of mine.